Upaya Pengembangan Lenong Betawi sebagai Atraksi Wisata Budaya di Setu Babakan - Fenella Julya Aziahra; Dyah Mustika Wardani; Gilang Fahreza (Tamasya : Jurnal Pariwisata Indonesia, 2026)
Lenong Betawi is a traditional performing art rooted in Betawi culture, with strong cultural value and real potential as a cultural tourism attraction. This study explores how Lenong Betawi could be further developed at Setu Babakan Betawi Cultural Village using the 4A tourism framework. A qualitative descriptive approach was used, with data gathered through observations, interviews, and documentation. The analysis focused on the four key elements: Attraction, Accessibility, Amenities, and Ancillary Services, to understand both the strengths and the challenges surrounding its development. The findings suggest that Lenong Betawi is a proper crowd-puller, offering visitors both entertainment and a chance to learn about Betawi culture. Setu Babakan also ticks the right boxes, with decent accessibility, solid visitor facilities, and strong backing from both the local community and the government to help keep Betawi traditions alive. These findings are expected to provide recommendations for stakeholders in developing more sustainable cultural tourism attractions while strengthening the preservation and promotion of Betawi cultural heritage.